The Potential of Natural Antioxidants as Feed Additives on the Quantity and Quality of Quail Products - Nissa, Aulia Khoirun; Anggaeni, Trianing Tyas Kusuma; Wulandari, Eka (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2022)
The demand for Japanese quail products continues to increase because they contain a good nutrient source for human health. There is an increase in environmental pollution where quail is susceptible to Pb exposure even in an intensive rearing system. Heavy metal Pb can accumulate in several body tissues, causing oxidative stress and tissue damage, affecting bird health, and impacting production performance and product quality. This review aimed to discuss the potential and mechanism of natural antioxidants as feed additives in Japanese quail on the quantity and quality of their products. Alpha-lipoic acid and Yucca schidigera in feed reduced Pb residues in body tissues by increasing the body's antioxidant system and chelating activity. Phenolic compounds are plants' most significant group of compounds belonging to natural antioxidant compounds. Phenolic compounds in turmeric, ginger, pomegranate peel, thyme, cinnamon, seaweed, and moringa seeds in feed increase the quantity or quality of eggs by protecting the reproductive organs, liver, and digestive tract from oxidative damage and improving the function of these organs to egg formation. Phenolic compounds in cinnamon, thyme, peppermint, and oyster mushrooms in feed improved meat quality by preventing lipid and protein oxidation in muscles. Using natural antioxidants as feed additives in Japanese quail can reduce Pb residues, increase egg quantity and quality, and improve meat quality with different mechanisms of action according to the source of natural antioxidants and their intended use.